Geniposide prevents H2O2‐induced oxidative damage in melanocytes by activating the PI3K–Akt signalling pathway. (7th March 2018) - Lu, W.; Zhao, Y.; Kong, Y.; Zhang, W.; Ma, W.; Li, W.; Wang, K.
Summary: Background: Oxidative stress is one possible pathogenic event in vitiligo that induces melanocyte destruction. Geniposide exerts certain antioxidant effects on various cells by activating the phosphoinositol 3‐kinase (PI3K)–Akt signalling pathway. However, researchers have not clearly determined whether geniposide protects human melanocytes from oxidative stress or identified the underlying mechanism of such protection. Aim: To determine whether geniposide protects melanocytes from H2 O2 ‐induced oxidative damage and to explore the role of the PI3K–Akt signalling pathway in this protective effect. Methods: The antioxidant effects of geniposide on human melanocytes were examined by measuring cell viability, apoptosis rates, reactive oxygen species (ROS) production and activities of the antioxidant enzymes superoxide dismutase (SOD) and catalase (CAT). We examined expression of Akt, phosphorylated Akt (p‐Akt), Bcl‐2, Bax, and cleaved caspase 3 and cleaved caspase 9 proteins to determine the involvement of the PI3K–Akt pathway. Results: Pretreatment with geniposide 5, 25, 125 or 625 μmol/L increased cell viability and decreased the apoptosis rate of H2 O2 ‐treated melanocytes. In addition, geniposide enhanced the antioxidant activity of SOD and CAT, and decreased intracellular ROS accumulation. Furthermore, geniposide increased the levels of p‐Akt and regulated the expression of downstream proteins in the PI3K–Akt pathway, such as Bcl‐2, Bax, and cleaved caspase 3 and 9, in H2 O2 ‐treated melanocytes. Notably, these effects were largely blocked by treatment with LY294002 prior to H2 O2 treatment. Conclusions: Based on these results, geniposide protects human melanocytes from H2 O2 ‐induced oxidative damage, and the PI3K–Akt signalling pathway is involved in its antioxidant effect.